2017
DOI: 10.1515/ijamh-2016-0149
|View full text |Cite
|
Sign up to set email alerts
|

Bullying, its effects on attitude towards class attendance and the contribution of physical and dentofacial features among adolescents in Northern Nigeria

Abstract: Background Bullying is a worldwide problem with varying consequences. Victims of school bullying may be targeted for many reasons including their appearance. They may also fear school and have difficulties in concentration. Objective This study aimed to determine the prevalence of bullying amongst adolescents in Kano, Northern Nigeria, the contribution of physical features and the perceived effect of bullying on their academic performance and school attendance. Subjects and methods Eight hundred and thirty-fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
36
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(54 citation statements)
references
References 15 publications
8
36
1
5
Order By: Relevance
“…These results agree with those reported by Chikaodi et al 4 and Oliveiros et al 6 who found that general bullying is more frequent in public schools. These authors 6 reported that school bullying was characterized by name-calling, followed by physical aggression, and thirdly by discrimination.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results agree with those reported by Chikaodi et al 4 and Oliveiros et al 6 who found that general bullying is more frequent in public schools. These authors 6 reported that school bullying was characterized by name-calling, followed by physical aggression, and thirdly by discrimination.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also coincide with those of Chikaodi et al 4 who reported no differences between females and males. It is possible that the similarity between the two groups can be attributed to the fact that there are other factors more relevant than sex, such as greater economic control, relationship with physical punishment, consumption of tobacco, alcohol and drugs, and even having already had sexual relationships.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study has shown that bullying victimization is highly prevalent in Saudi schools. The estimated prevalence (89.2%) could be the highest amongst studies carried out in the Middle East and across the globe [6,8,[10][11][12]27]. However, when the prevalence of the condition is considered separately for each age group, the prevalence estimate for children younger than 12 years of age in the current study (73.7%) was just slightly lower than that reported in Jordan (80%) [8].…”
Section: Discussioncontrasting
confidence: 69%
“…In the current study, a questionnaire was preferred over interviews as an assessment tool for purposes of enabling comparisons with different countries that used questionnaires because of the sensitivity of the topic. [8,10,27] It was previously reported that denial of the bullying condition, which should be embarrassing when confronted about, would be less in questionnaires as compared to direct interviews. [10] The questionnaire began with a clear definition of bullying, and the forms of bullying included examples to minimize the subjectivity and bias that may result from self-perceptions of bullying victimization [28].…”
Section: Discussionmentioning
confidence: 99%